Donation after Brain Death versus Donation after Circulatory Death: Lung Donor Management Issues - Snell, Gregory I.; Levvey, Bronwyn J.; Levin, Kovi; Paraskeva, Miranda; Westall, Glen (Seminars in Respiratory and Critical Care Medicine, 2018)
Lung transplantation (LTx) has traditionally been limited by a lack of suitable donor lungs. With the recognition that lungs are more robust than initially thought, the size of the donor pool of available lungs has increased dramatically in the past decade. Donation after brain death (DBD) and donation after circulatory death (DCD) lungs, both ideal and extended are now routinely utilized. DBD lungs can be damaged. There are important differences in the public's understanding, legal and consent processes, intensive care unit strategies, lung pathophysiology, logistics, and potential-to-actual donor conversion rates between DBD and DCD. Notwithstanding, the short- and long-term outcomes of LTx from any of these DBD versus DCD donor scenarios are now similar, robust, and continue to improve. Large audits suggest there remains a large untapped pool of DCD (but not DBD) lungs that may yet further dramatically increase lung transplant numbers. Donor scoring systems that might predict the donor conversion rates and lung quality, the role of ex vivo lung perfusion as an assessment and lung resuscitation tool, as well as the potential of donor lung quality biomarkers all have immense promise for the clinical field.
Keywords: lung transplantation; organ donation; donor management; donation after brain death; donation after circulatory death